A Correlation between Students’ Anxiety Levels and Oral Presentation Performance in EFL Speaking Class - Aisyah Amini; Elfrida .; Kasmaini . (Universitas Bengkulu, 2019)
ABSTRACTThis research was aimed to find out whether there is a correlation between students’ anxiety level and oral presentation’s performance in EFL speaking class. The population of this research was the 4th semester students in English Education Study Program of Bengkulu University class A, B and C with 51 students randomly chosen as the sample. The design of this research was descriptive quantitative with questionnaire and presentation test as the instruments. The questionnaire of this research was FLCAS (Foreign Language Classroom Anxiety Scales) by Horwitz (1986) meanwhile the presentation test was a presentation test rubric evaluated by two raters in order to find the reliability of the test. The result of this research showed that there was a significant negative correlation between students’ anxiety level and oral presentation test score from rater 1 and rater 2. Based on the result, the strength of this correlation was moderate. On the other hand, both of the results were in negative directions. The finding also showed that most of the students had “Mildly Anxious” level of anxiety and “Basic” category from presentation test score. It can be concluded that anxiety can influenced the students’ speaking skill especially while performing a presentation in front of the class. Some factors as like fear of making mistakes, being seen by a lot of people, or being interrupted by the lecturers can increase the students’ anxiety. Keywords : Anxiety Levels, Oral Presentation, Speaking.